PENGEMBANGAN USAHA BENIH JAGUNG TAHAN KERING - Sarwadana, S.M.; Putri, B.R.T.; Dinata, K.K. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana Mengabdi, 2018)
Activities of science and technology for innovation and creativity campus aims are: (1) the commercialization of science and technology campus creativity as a source of financing for the development of institutions; (2) stimulate the entrepreneurial spirit among beings campus, and (3) help people get seeds of drought-tolerant maize varieties. Methods of execution include the business aspects of the planned business activities consist of: provision of raw materials, production processes, management, marketing, human resources, facilities, and financial. The raw material is obtained from units of science and technology for novation and creativity campus and through partnerships with farmers' seed corn. The production process started from seed, sorting, and packaging. Marketing is done directly, partnerships with local governments and konsiniasi with kiosk / farm shop. Results show that the activities of science and technology unit for innovation and creativity campus drought-tolerant maize seed has gone well characterized by support infrastructure adequate maize seed production; IbIKK unit operates under the management of PS Agroecotechnology Faculty of Agriculture, University of Udayana; Of investment made in 2014 amounting to Rp. 39,550,000; Result of sales corn seeds turnover in 2014 amounted to 400 kg (Rp. 12 million); and net cash flow amounted to 17,672,400.